2020
DOI: 10.1002/jsfa.10751
|View full text |Cite
|
Sign up to set email alerts
|

Effect of κ‐carrageenan addition on protein structure and gel properties of salted duck egg white

Abstract: BACKGROUND Salted duck egg white (SDEW) is a major by‐product during salted egg yolk manufacturing. Due to the high salt concentration, SDEW has not been efficiently utilized. Moreover, functional properties of SDEW are altered by salt during pickling. To improve the functional properties, the effect of κ‐carrageenan (κ‐CAR) addition on the protein structure and gel properties of SDEW was investigated in this study. RESULTS The surface hydrophobicity and free sulfhydryl content of SDEW protein increased, while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 44 publications
1
17
0
Order By: Relevance
“…Many reports have indicated the interaction between protein and KC or XG. KC has a good synergistic effect with a variety of proteins, such as whey protein isolate , salted duck egg white (Tang et al, 2020), egg yolk protein (Huang et al, 2021), myofibrillar protein (Zhang et al, 2017), and antarctic krill protein isolated (Zheng et al, 2019). The addition of XG also could enhance gel properties of protein, such as ovalbumin (Souza & Garcia-Rojas, 2016) and whey protein isolate (Geremias-Andrade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many reports have indicated the interaction between protein and KC or XG. KC has a good synergistic effect with a variety of proteins, such as whey protein isolate , salted duck egg white (Tang et al, 2020), egg yolk protein (Huang et al, 2021), myofibrillar protein (Zhang et al, 2017), and antarctic krill protein isolated (Zheng et al, 2019). The addition of XG also could enhance gel properties of protein, such as ovalbumin (Souza & Garcia-Rojas, 2016) and whey protein isolate (Geremias-Andrade et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Hydrophobic interactions, hydrogen bonds, and electrostatic interactions are noncovalent bonds, while disulfide bonds are covalent bonds. The hydrophobic interactions of proteins are influenced by surface hydrophobicity, which can stabilize the protein conformation and contribute to the formation of gel networks (Tang et al., 2020). Thus, the hydrophobic group inside the protein molecule is exposed by external factors to increase the surface hydrophobicity of the protein molecule and promote the formation of the gel.…”
Section: Mechanism Of Ep Gel Formation and Influence Factorsmentioning
confidence: 99%
“…2015). However, κ‐carrageenan addition decreased relative content of α‐helix and β‐turn and increased β‐sheet and random coil of salted duck egg white (Tang et al., 2020). It may be because duck egg white gels contained many salt ions that changed protein conformation.…”
Section: Effect Of Polysaccharides On the Functional Properties Of Ewpmentioning
confidence: 99%
“…In addition, the egg white gel network also depended on environmental factors such as pH, ionic strength, and temperature. For example, high NaCl concentrations influenced aggregation behavior of duck egg white protein and had adverse effects on its textural properties (Tang et al., 2020). Deng et al., (2020) showed that K + significantly enhanced the gel properties, while Ca 2+ , Zn 2+ , and Fe 3+ were more conducive to formation of polymers to affect gel performance of alkali‐induced EWP.…”
Section: Functional Properties Of Ewpmentioning
confidence: 99%